Development of HistoVIR: Immersive Learning Media Based on Virtual Reality for History on Senior High School - Listyanto Aji Nugroho; Emy Wuryani (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2026)
This study aims to explore the effectiveness of using a Virtual Reality (VR)-based learning tool, histoVIR, in enhancing students' understanding and engagement in history lessons at Senior High School of Kristen Satya Wacana. Utilizing the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation, this research focuses on meeting students' unique needs through accessible and interactive media. The analysis phase revealed gaps in the availability of adaptive learning resources and technology at the school, highlighting the need for more tailored learning tools. In the design and development stages, histoVIR was created by integrating text, audio, and visual elements to provide an immersive and culturally relevant learning experience. Feedback from media experts and teachers confirmed that the tool was effective in enhancing student engagement and facilitating understanding of historical content. The implementation phase showed an increase in student participation and improvement in comprehension, as reflected in improved test scores after using the media. This study confirms that adaptive technologies, such as VR, can support inclusive education, particularly for students with diverse learning needs. The findings provide a promising model for the development of VR-based learning tools in inclusive educational settings.